Identification of a Fetal De Novo Splice Variant in ARCN1 Associated With Growth and Skeletal Abnormalities - Wencong He; Zejun Yang; Jianjian Cui; Ruilin Ma; Hui Tao; Yanan Li; Yin Zhao; Yang Pan; Jue Li (Maternal-Fetal Medicine)
Abstract. Objective:. To report a fetus with ARCN1-related syndrome caused by a novel de novo heterozygous variant, highlighting the importance of early genetic diagnosis in prenatal care. Methods:. The clinical and genetic data of a fetus with a complex combination of clinical signs and a novel de novo heterozygous variant were collected and have been summarized in this study. The potential pathogenic variant was identified throughout the whole exome sequencing and the effects of candidate variants were further validated by a minigene splicing assay. Results:. Prenatal systematic ultrasound detected fetal growth restriction. Genetic analysis identified a novel de novo heterozygous variant within the ARCN1 gene—c.1241+5G>A—located in intron 8. In vitro minigene splicing assays demonstrated that the variant led to two abnormal transcripts. The longer transcript retained 189 base pairs of intron 8, resulting in a truncated protein of 414 amino acids (p.Ser415*). The shorter transcript involved exon 8 skippings, producing a truncated protein of 407 amino acids (p.Ile378Serfs*31). Conclusion:. A novel de novo heterozygous variant of the ARCN1 gene, namely NM_001655.5: c.1241+5G>A, was discovered and identified in a fetus with rhizomelic short stature, microretrognathia, and developmental delays.